(untitled) (Bangladesh Journal of Infectious Diseases, 2022)
Background: The authenticity and importance of RT-PCR testing cannot be overstated, for resource-limited settings like Bangladesh, especially in places where RT -PCR facilities are unavailable, rapid antigen testing could be an important supportive tool in SARS-CoV-2 diagnosis. Objective: The aim of this study was to compare rapid SARS-CoV-2 antigen detection test with RT-PCR for viral gene detection assay. Methodology: This cross-sectional study was performed at National Institute of Laboratory Medicine and Referral Center (NILMRC), Dhaka between March and April 2021. The nasopharyngeal swab samples were obtained from COVID-19 suspected cases collected from NILMRC virology lab. RT-PCR testing was conducted by Novel Coronavirus Nucleic Acid Diagnostic Kit. Rapid antigen testing was conducted using Standard Q COVID-19 Ag test. Results: The median age was 35.2 years. Among the confirmed cases, 63.0% were male patients. A total of 68 samples came out as positive and 226 were negative using both methods. Additionally, four more positive cases were detected by the Rapid Antigen Testing method. The sensitivity and specificity of the rapid antigen test was found to be 94.0% and 99.0% respectively. Conclusions: Rapid antigen test and rt-PCR showed almost similar sensitivity and specificity. Bangladesh Journal of Infectious Diseases, April 2022;9(Suppl_1): S24-S27